TEACHING ENGLISH READING MATERIALS THROUGH TEAM-BASED-PROJECT IN SMPN 4 BISSAPPU - Sari, Suci Indah; Maharida; Saiful (FKIP Unismuh Makassar, 2023)
This study aims to improve students' reading ability related to understanding main ideas and supporting ideas. This research is quantitative research. The subjects of this study were students of class VIII.. In analyzing the data, researchers used data reduction, data presentation, and data verification. This research is a pre-experimental design research using pre-test and post-test. The population in this study were students of class VIII SMP Negeri 4 Bissappu and for sampling the researchers used random sampling. The research sample was 25 students.The results of the data show that there is a difference between the students' pre-test and post-test. The main score of the students before being given treatment was 52.5 and increased to 80.36 after applying the Team-Based-Project. In addition, from the t-test analysis, the t-test value is greater than the t-table, the students' total vocabulary mastery (8.34>1.714).